Conflicting signal in transcriptomic markers leads to a poorly resolved backbone phylogeny of chalcidoid wasps. (9th February 2020) - Zhang, Junxia; Lindsey, Amelia R.I.; Peters, Ralph S.; Heraty, John M.; Hopper, Keith R.; Werren, John H.; Martinson, Ellen O.; Woolley, James B.; Yoder, Matt J.; Krogmann, Lars
Abstract: Chalcidoidea (Hymenoptera) are a megadiverse superfamily of wasps with astounding variation in both morphology and biology. Most species are parasitoids and important natural enemies of insects in terrestrial ecosystems. In this study, we present a transcriptome‐based phylogeny of Chalcidoidea; we found that poorly resolved relationships could only be marginally improved by adding more genes (a total of 5591) and taxa (a total of 65), proof‐checking for errors of homology and contamination, and decreasing missing data. Concatenation analyses consistently place Mymaridae and Trichogrammatidae sister to remaining Chalcidoidea. However, our coalescent analyses provide a different hypothesis with a grouping of (Mymaridae (((Trichogrammatidae, Eulophidae), (Encyrtidae, Aphelinidae)), remaining Chalcidoidea)). This hypothesis complicates our hypothesis of egg parasitism as being the ancestral state in Chalcidoidea. At the deeper nodes, the results uncovered a wide spectrum of gene discordance in the transcriptomic markers and identified a strong signal of functional bias in genes supporting alternative phylogenies. These deeper nodes of the phylogeny are thus strongly influenced by biased support from different functional gene complexes. Shallower nodes showed similar gene discordance, but without strong functional bias. Understanding and identifying mechanisms that result in gene tree discordance may be beneficial and even essential for elucidating deeper relationships, especially for groups that have undergone extremely rapid radiation. Abstract : Concatenation and coalescent analyses recover competing backbone relationships of Chalcidoidea, which complicates our hypothesis of egg parasitism as being the ancestral state in Chalcidoidea. A wide spectrum of conflicting signal accounts for the poorly supported backbone phylogeny of Chalcidoidea. Functional bias is present in genes supporting alternative relationships at the deeper nodes of the chalcidoid phylogeny.